Evaluación del crecimiento de especies forestales en plantaciones para recuperación de áreas degradadas en la Región San Martín 2009 - Sánchez Angulo, José Isaías (2010)
This research paper presents information obtained during the months of January to December 2009, conducted with the aim of raising awareness of the importance of carrying out assessments of forest growth in the region of San Martin, so better decisions are taken management of forest plantations, as this investigation we will acknowledge that forest species are adapted quickly to different climates, soils, etc. to recover degraded areas. Assessments made after growth of forest species in the study areas, we can state that must perform maintenance and management of plantations evaluated and used in reforestation programs forest species Teak (Tectona grandis) for its good growth all areas assessed. We can see that the diameter and height of 20 plants of each tree species tested, better growth was obtained and an increase in forest species of Teak (Tectona grandis) with DBH of 9.49 cm and a height of 6.85m, and increased DBH of 0.64 cm and a height of 0.32 m Bolaina (Guazuma crinita) with DBH of 9.87 cm and a height of 6.86 m, and DAP increased from 0.55 cm and a height of 0.36 m, in the Province of Lamas - Alliance , The diameter and height of 20 plants of each tree species tested, better growth was obtained in the pink cedar forest species (Agrocarpus flaxinifolius) with DBH of 8.46 cm and a height of 6.39 m, and the species best increase had been the Shaina (Colubrina glandulosa) with DBH of 1.04 cm and a height of 0.62 m, in the province of San Martin - Tarapoto, the diameter and height of 20 plants of each forest species evaluated, better growth was obtained in the forest species Teak (Tectona grandis) with DBH of 4.23 cm and a height of 3.46 m, and DAP increased 0.27 cm and a height of 0.15 m in the province of Rioja, the diameter and height of 20 plants of the forest Teak (Tectona grandis) evaluated, showed a growth of DAP, 7.68 cm and a height of 6.17 m, and DAP increased 0.22 cm and a height of 0.15 m. In the province of Mariscal Cáceres (Juanjui) diameter and height of 20 plants of the forest species Mahogany (Swietenia macrophylla) evaluated, showed a growth of DBH of 9.15 cm and a height of 5.84 m. and DAP increased 0.10 cm and a height of 0.06 m. In the province of Huallaga (Saposoa).